2017
DOI: 10.1007/s12602-017-9267-9
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibition Effect of Lactobacilli Against Growth and Biofilm Formation of Pseudomonas aeruginosa

Abstract: The emergence of antibiotic-resistant and food-spoilage microorganisms has renewed efforts to identify safe and natural alternative agents of antibiotics such as probiotics. The aim of this study was the isolation of lactobacilli as potential probiotics from local dairy products with broad antibacterial and anti-biofilm activities against antibiotic-resistant strains of Pseudomonas aeruginosa and determination of their inhibition mechanism. Antibiotic susceptibility and classification of acquired resistance pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
82
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(91 citation statements)
references
References 34 publications
7
82
1
1
Order By: Relevance
“…In summary, this report describes a therapeutic strategy using probiotics and aPDT for the treatment of external ear canal infection and gut decolonization of a high‐risk clone of VIM‐2‐producing P. aeruginosa in a dog. These findings support the results of previous studies that have shown lactobacilli‐based probiotics to be effective against planktonic and biofilm modes of growth of MDR P. aeruginosa clinical isolates …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In summary, this report describes a therapeutic strategy using probiotics and aPDT for the treatment of external ear canal infection and gut decolonization of a high‐risk clone of VIM‐2‐producing P. aeruginosa in a dog. These findings support the results of previous studies that have shown lactobacilli‐based probiotics to be effective against planktonic and biofilm modes of growth of MDR P. aeruginosa clinical isolates …”
Section: Discussionsupporting
confidence: 91%
“…have been investigated as candidates to reduce gut colonization by multidrug‐resistant (MDR) pathogens. Probiotics can act as microbial barriers through competitive inhibition of pathogen binding sites and prevention of the production of virulence factors, and have shown promising results in laboratory mice . In addition, the use of prebiotics (nutritional ingredients) combined with probiotics could be a tool against MDR‐related colonization, reestablishing the normal gut microbiota …”
Section: Introductionmentioning
confidence: 99%
“…The inhibitory compounds produced by lactobacilli include organic acids such as lactic acid, acetic acid, and formic acid or bacteriocins. 8,9 Through these antimicrobial mechanisms, lactobacilli have demonstrated antagonistic activates against different pathogenic bacteria, including carbapenem-resistant Enterobacteriaceae, 10 Escherichia coli, 11 Helicobacter pylori, 12 Salmonella, 13 Shigella, 14 P aeruginosa, 15 and Staphylococcus aureus. 16 However, no previous studies have assessed the antimicrobial activity of lactobacillus against ESBL-producing K pneumoniae or P aeruginosa.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have screened beneficial bacteria for the natural competitors of pathogenic bacteria in order to prevent colonization or biofilm formation by the latter. Lactobacilli have been extensively studied in this regard because of their remarkable ability to inhibit the growth of pathogenic bacteria by producing bactericidal compounds such as lactic acid as a metabolic by-product, which also includes hydrogen peroxide, diacetyl, and bacteriocin 7,8 . Lactobacillus acidophilus and Lactobacillus fermentum produce antimicrobial compounds that not only inhibit bacterial growth but also inhibit biofilm formation of K. pneumoniae 9 .…”
Section: Introductionmentioning
confidence: 99%